Interactive M-Learning Design Innovation using Android-Based Adobe Flash at WFH (Work From Home) - Voutama, Apriade; Maulana, Iqbal; ade, Nofri; Rizal, Adhi (Universitas Negeri Semarang, 2021)
Purpose: The benefits of technology in education are among the essential factors in the Work From Home (WFH) period. One of these learning media innovations is the design of mobile-based interactive M-Learning. Interactive M-Learning is a dynamic learning technology where the learning process contains theory and questions and features animation, game interaction, and sound and video. Methods: The learning revolution from computers to mobile is an effective way because the mobility and network connections that have been presented on mobile devices make it easier for users to access information as proposed by Mushtaq. Interactive M-Learning applications are designed with UML (Unified Modeling Language) modeling by utilizing several diagrams such as Usecace, Activity, Sequence, Class Diagram to determine the actors involved in the description of the activities that occur in the use of the M-Learning system. Result: The design results are translated into an application using Adobe Flash and then implemented on Android mobile devices. Adobe Flash is software used to create images and animations. The results of M-Learning, which have become an application, provide convenience in the distance learning process with a concept. Novelty: It does not provide simple learning but is also attractively designed.